Pengembangan Model Rantai Pasok Minyak Goreng Untuk Meningkatan Produktivitas Menggunakan Sistem Dinamik pada PT XYZ - Donaya Pasha; Erma Suryani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2017)
Constituent elements of the supply chain system of PT XYZin this study consists of a supplier, manufacturer, and consumers. On the supply chain manufacturers, the production of cooking oil menglami deficit against the demand for cooking oil in the country. That is because the existence of factors such as productivity decline in the influence of the type of seeds are used, the age of the plant, and the process of rainfall harvesting faction TBS uneven. This proposed research on the development model of the supply chain to improve the productivity of cooking oil using dynamical systems. The proposed method consists of three main stages, the first stage of the modelling system Modeler concept of causal loop diagrams. The second stage is a causal loop diagram for the model of dynamic systems. The last stage is the formulation of the model to determine the dynamic behavior caused by the assumptions of the model. The results of this research are the development of a supply chain model of cooking oil to increase productivity using dynamic systems. The results of the simulation scenario, the proposed method is successfully increasing the productivity of the TBS of 17.6% (tons) per hectare per year and the production of cooking oil are having a surplus with an average 30.31%